Optimasi Media Transmisi Nirkabel Pada Controlling Alat Elektronik Smart Home dengan Xbee Module Berbasis Arduino Uno - Lase, Kristian Juri Damai; Setyawan, Gogor C.; Masoino, Stevie (STIKOM Tunas Bangsa Pematangsiantar, 2024)
Smarthome is a smart home system that connects communication networks with electronic equipment so that it can be controlled, monitored or accessed remotely. Smarthome can also increase efficiency, comfort and security by using technology automatically. This study aims to determine the use of Xbee Module as a wireless transmission medium for controlling smart home electronic devices. The method used in this research is literature study, analysis and design, implementation and testing, the author designs a local network with a basic configuration using wireless media to create a local network to be connected to each other both Xbee Transmitter and Xbee Receiver so that both can be connected and can communicate in the same frequency channel or network. Based on the test results, it is found that the use of Xbee Module as a wireless transmission medium to control smart home electronic devices works well at a maximum distance of 80 meters.